Translators Educational Perspective in Accession Country - Kučiš, Vlasta (Array, 2012)
Education for translator´s profession requires not only, language, knowledge and skills, but also intercultural communication, the use of ICT, terminology work, project management, translation theory and language culture, as defined by the European Master´s Translation which combines different teaching methods.